Icariin-Loaded Hydrogel Regulates Bone Marrow Mesenchymal Stem Cell Chondrogenic Differentiation and Promotes Cartilage Repair in Osteoarthritis - Zhu, Yuefeng; Ye, Le; Cai, Xiaoxi; Li, Zuhao; Fan, Yongqian; Yang, Fengjian (Frontiers in Bioengineering and Biotechnology, 2022)
Intra-articular injection of mesenchymal stem cells is a potential therapeutic strategy for cartilage protection and symptom relief for osteoarthritis (OA). However, controlling chondrogenesis of the implanted cells in the articular cavity remains a challenge. In this study, hydrogels containing different concentrations of icariin were prepared by in situ crosslinking of hyaluronic acid and Poloxamer 407. This injectable and thermoresponsive hydrogel, as a 3D cell culture system, showed good biocompatibility with chondrocytes and bone marrow mesenchymal stem cells (BMSCs), as well as promoted proliferation and chondrogenesis of BMSCs through the Wnt/β-catenin signaling pathway. Intra-articular injection of this kind of BMSC-loaded composite hydrogel can significantly prevent cartilage destruction by inducing chondrogenic differentiation of BMSCs, and relieve pain through regulating the expression of inflammatory cytokines (e.g., IL-10 and MMP-13) in the OA model. Incorporating BMSCs into this novel icariin-loaded hydrogel indicates a more superior efficacy than the single BMSC injection, which suggests a great potential for its application in OA.